2013
DOI: 10.1007/s10120-013-0280-8
|View full text |Cite
|
Sign up to set email alerts
|

Limited subtotal gastrectomy for early remnant gastric cancer

Abstract: Background Detection of early remnant gastric cancer (ERGC) is increasing as a result of the development of endoscopic technology and a surveillance program. The aim of this study was to evaluate the results of limited subtotal gastrectomy (SG) surgery for ERGC compared to total gastrectomy (TG). Methods We retrospectively reviewed a database of 72 consecutive patients with remnant gastric cancer who underwent laparotomy at the National Cancer Center Hospital East between January 1993 and December 2008. Thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…Because of anatomical alterations and intra-abdominal adhesions, surgical treatments for GSC are difficult and are associated with relatively high rates of morbidity and mortality [7]. Yuichi Hosokawa et al [15] and Tomoyuki Irino et al [16] found a similar frequency of complications in the SG and TG groups for GSC. In the present study, we also found that the rate of complications was similar in the two groups; however, there were three cases of anastomotic leakage in the TG group and no cases of anastomotic leakage in the SG group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of anatomical alterations and intra-abdominal adhesions, surgical treatments for GSC are difficult and are associated with relatively high rates of morbidity and mortality [7]. Yuichi Hosokawa et al [15] and Tomoyuki Irino et al [16] found a similar frequency of complications in the SG and TG groups for GSC. In the present study, we also found that the rate of complications was similar in the two groups; however, there were three cases of anastomotic leakage in the TG group and no cases of anastomotic leakage in the SG group.…”
Section: Discussionmentioning
confidence: 99%
“…Seung Lee et al investigated long-term differences in QoL after SG and TG by comparing two groups and found an inferior QoL stemming from symptomatic and behavioral consequences of surgery in survivors 5 years after TG [27]. Regarding GSC, Yuichi Hosokawa et al [15] compared SG and TG for GSC in 13 and 22 patients, respectively, and found that three patients in the TG group developed dumping syndrome, while no patients in the SG group developed dumping syndrome. Additionally, the hemoglobin and total protein levels were higher in the SG group than in the TG group 1 year after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, all of these questionnaires are thought to lack sensitivity to treatment interventions, indicating the need for a specific patient-reported outcome questionnaire to be developed for dumping syndrome. There is agreement that the modified OGTT is the preferred diagnostic method (statement 33), and diagnostic parameters for early and late dumping syndrome are well established (statements [34][35][36]. The same glycaemia level cut-off (50 mg/dl) is proposed for spontaneous glycaemia levels and for late hypoglycaemia during the modified OGTT for supporting the diagnosis of dumping syndrome (statements 28, 29, 35 and 36).…”
Section: Recommendationsmentioning
confidence: 99%
“…Em relação as recidivas, a recorrência em linfonodos mediastinais foi de dois pacientes dos treze que tiveram recidivas no mediastino, observando um melhor controle loco-regional. Hosokawa et al 91…”
Section: Análise Estatísticaunclassified